An intelligent insole system with personalised digital feedback reduces foot pressures during daily life: An 18-month randomised controlled trial. (November 2021) - Chatwin, Katie E.; Abbott, Caroline A.; Rajbhandari, Satyan M.; Reddy, Prabhav N.; Bowling, Frank L.; Boulton, Andrew J.M.; Reeves, Neil D.
Highlights: An insole system continuously monitors daily plantar pressure for 18 months. Personalised pressure feedback reduces foot pressure in feet at high-risk of ulcers. Pressure feedback induced a learning response. Abstract: Aims: High plantar pressure is a major risk factor in the development of diabetic foot ulcers (DFUs) and recent evidence shows plantar pressure feedback reduces DFU recurrence. This study investigated whether continued use of an intelligent insole system by patients at high-risk of DFUs causes a reduction in plantar pressures. Methods: Forty-six patients with diabetic peripheral neuropathy and previous DFU were randomised to intervention (IG) or control groups (CG). Patients received an intelligent insole system, consisting of pressure-sensing insoles and digital watch. Patients wore the device during all daily activity for 18-months or until ulceration, and integrated pressure was recorded continuously. The device provided high-pressure feedback to IG only via audio-visual-vibrational alerts. High-pressure parameters at the whole foot, forefoot and rearfoot were compared between groups, with multilevel binary logistic regression analysis. Results: CG experienced more high-pressure bouts over time than IG across all areas of the foot ( P  < 0.05). Differences between groups became apparent >16 weeks of wearing the device. Conclusions: Continuous plantar pressure feedback via an intelligent insole system reduces number of bouts of high-pressure in patients at high-risk of DFU. These findings suggest that patients were learning which activities generated high-pressure, and pre-emptively offloading to avoid further alerts.